2016
DOI: 10.1142/s0219519416500329
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of High Strain Rate Responses of Porcine Brain, Liver, and Tendon

Abstract: High strain rate compression of soft tissues has recently gained attention due to its application in computational simulation of traumatic injuries. To understand high rate tissue behavior, a comparative study is needed to examine the biomechanical responses of multiple soft tissues. We hypothesized that the underlying mechanisms of soft tissue high rate compression is dependent upon water, microstructural organization, and extracellular matrix (ECM). Porcine brain, liver, and tendon, which have similar materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…This study indicates that damage patterns under high tensile strains exhibited the most pronounced lacerations, which complements reports that describe tensile stress as the main contributor to liver lacerations frequently observed in traumatic abdominal injuries [49]. The damage evolution under compression loads is different so that it endures compression loads much better than tension and shear.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study indicates that damage patterns under high tensile strains exhibited the most pronounced lacerations, which complements reports that describe tensile stress as the main contributor to liver lacerations frequently observed in traumatic abdominal injuries [49]. The damage evolution under compression loads is different so that it endures compression loads much better than tension and shear.…”
Section: Discussionsupporting
confidence: 86%
“…In all of these samples, the capsule was removed and testing was done solely on the liver parenchyma. Furthermore, directionality was not considered in our extracted samples, because liver tissue has been shown to exhibit an isotropic mechanical response to mechanical testing [32,49,50]. Control histology samples (n ¼ 2 per liver) were taken in a similar fashion using the shear sample stamp and used as a global control for all tests.…”
Section: Sample Preparation and Experiments Designmentioning
confidence: 99%
“…It is interesting to note that high strain rate testing of different tissues results in different degrees of initial stiffening. The results obtained by Prabhu et al for brain tissue and by Clemmer et al for liver tissue at high rate compression demonstrated a higher initial hardening peak when compared to liver data reported in this study [23,24]. The above observation leads to a hypothesis correlating the initial stiffening with concentration of cellular content/water content [23].…”
Section: Discussionsupporting
confidence: 70%
“…High strain rate testing was performed as per previously established protocol [23,24,25]. The PSHPB, made of commercially extruded natural polycarbonate (PC 1000) rods, was composed of a striker bar, an incident bar, and a transmitted bar with lengths of 0.762, 2.438, and 1.219 m, respectively, and a diameter of 38.1 mm (Figure 2a).…”
Section: Methodsmentioning
confidence: 99%
“…However, in a recent study on the dynamic response of the brain, part of the inertial effects was shown to be intrinsic to the material and that non-uniform stress-states were realized in the material [29]. As a major component of the brain, water proved crucial in instigating the initial hardening [29,30]. To date, no researcher has analyzed the effect of the amount of water within the brain that has undergone high impact loads.…”
Section: Introductionmentioning
confidence: 99%